Financial Markets and Services. - Gordon, E. (Himalaya Pub. House, 2009)
Financial markets have been increasingly influenced in recent times by financial innovations in terms of products and instruments, adoption of modern technologies, opening up of the market to the global economy, streamlining of the regulatory framework and so on. Similarly many innovative financial products are introduced to cater to the varied requirements of both corporate and individual customers, In the aftermath of this changing financial scenario, students of commerce and management are badly in need of a suitable text-book covering all these aspects incorporating the latest developments.